The infectious thyroid nodule: a case report of mucormycosis associated with ibrutinib therapy - Marco A. Mascarella; Lorne Schweitzer; Mahmoud Alreefi; Jennifer Silver; Derin Caglar; Vivian G. Loo; Keith Richardson; Philippe Dufresne; Todd C. Lee; Nader Sadeghi (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Acute invasive fungal infections of the head and neck secondary to tyrosine kinase inhibitors are rare and potentially life-threatening events. Case presentation We report a case of mucormycosis of the thyroid gland in a patient known for chronic lymphocytic leukemia receiving ibrutinib who presented with a rapidly growing thyroid nodule and dysphonia. An acute invasive fungal infection was identified on a core needle biopsy; mucormycosis was confirmed on culture. The patient was successfully treated with surgical debridement and long-term antifungal therapy. Conclusion Patients on ibrutinib may be at risk of acute invasive fungal infections of the head and neck.